Low-Cost Solar Mobile Power System - RAJENDRAN, AISHWARYA; Zulkifli, Mardzulliana (Progress in Engineering Application and Technology, 2023)
From the beginning of human history, technology has been rising and continuing to evolve. A variety of technologies have been invented to make daily human life easier while preserving comfort, and virtually all technology has been developed requiring electric power. Alternative sources of energy are being pursued in the world today. Since Malaysia is located near to the equator, the country receives large and constant amount of solar energy during daytime. It would be a waste if this energy is not utilized for producing electrical energy. Following this, solar energy offers a promising solution to this search as it is a less polluting energy resource and can easily be converted into electricity through the usage of photovoltaic system.A portable solar power system would be able to create enough power source for the users in the previously specified location in remote, undeveloped areas without an energy grid, whether they were rural or urban. Model approaches for a renewable energy supply have been developed and demonstrated to meet the energy requirements of rural and urban people as well. However, in Malaysia this type of power resource is still seen as a new concept and research is still being done to produce an efficient and cost- effective. This paper will describe a novel system and prototype which is to implement and develop a portable power generation system based on solar renewable energy resources. This prototype functions solely based on the input of solar renewable energy plus the system can be monitored using the IoT Blynk mobile monitoring interface. In this paper, an experimental and creative method for giving users a sufficient real-time power supply has been put into action. This project effectively implements the hardware design.